2014
DOI: 10.1680/wama.12.00071
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of vortex structure in multi-horizontal submerged jets stilling basin

Abstract: A three-dimensional numerical simulation was carried out on the complex flow field in a stilling basin of multi-horizontal submerged jets (MHSJs) using the mixture renormalisation group κ–ε turbulence model. Emphasis was placed on the characteristics of the vortex structure in a stilling basin of MHSJs. The results show that vortices with horizontal axes under the main jets are more stable in a flood discharging through crests overflowing orifices and mid-discharge orifices than in a joint flood discharging th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Comparing three operating conditions in combination with Figure 9, it can be concluded that the time-average pressure and RMS of fluctuating pressure in the longitudinal direction along the x-axis are relatively small at the front of the stilling basin, and the turbulence of the water flow is very severe due to the presence of the horizontal vortex [18]. At the end of the swirling zone (I) and impinging zone (II), the RMS value gradually increases and reaches the peak value.…”
Section: Qualitative Analysis Of Longitudinal Distributionmentioning
confidence: 91%
See 1 more Smart Citation
“…Comparing three operating conditions in combination with Figure 9, it can be concluded that the time-average pressure and RMS of fluctuating pressure in the longitudinal direction along the x-axis are relatively small at the front of the stilling basin, and the turbulence of the water flow is very severe due to the presence of the horizontal vortex [18]. At the end of the swirling zone (I) and impinging zone (II), the RMS value gradually increases and reaches the peak value.…”
Section: Qualitative Analysis Of Longitudinal Distributionmentioning
confidence: 91%
“…The superposition of the horizontal and vertical axis vortex makes the fluctuating pressure characteristics of the stilling basin slab particularly complicated. Some scholars have studied the fluctuating pressure of the stilling basin by physical model tests or using the κ-ε turbulence model to determine the height of the drop, the depth of the stilling basin, and the length of the underflow [4,6,18,19]. Ferreri et al [20] studied the different types of hydraulic jumps that occur in a rectangular channel at drop and abrupt enlargement.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this work is to optimize a recently developed novel technique for energy dissipation, Multi-Horizontal-Submerged Jets (simplified as MHSJ). MHSJ have been studied and improved by many researchers in recent years [8][9][10][11][12][13][14][15][16][17]. It has been demonstrated that MSHJ possesses three main advantages when compared with the hydraulic jump, which is the traditional energy dissipater: (1) lower atomization; (2) a higher rate of energy dissipation; (3) more flexibility of gate-opening modes [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…

It is my pleasure to welcome you to the June issue of Water Management, which brings together a selection of papers, briefings and discussions on a diverse range of interesting topics. The subsequent four papers focus on complex flow dynamics generated in stilling basins by submerged jets (Zhang et al, 2014) and at reservoir intakes by free surface vortices (Sarkardeh et al, 2014); sanitation issues associated with portable sewage systems (Khan et al, 2014b); and water quality modelling in clean water distribution networks (Seyoum and Tanyimboh, 2014).The accurate determination of water surface profiles for gradually varied flow (GVF) is a classic hydraulic problem of significant importance to water engineers interested in determining the upstream and downstream influence of in-stream structures or works. The subsequent four papers focus on complex flow dynamics generated in stilling basins by submerged jets (Zhang et al, 2014) and at reservoir intakes by free surface vortices (Sarkardeh et al, 2014); sanitation issues associated with portable sewage systems (Khan et al, 2014b); and water quality modelling in clean water distribution networks (Seyoum and Tanyimboh, 2014).

The accurate determination of water surface profiles for gradually varied flow (GVF) is a classic hydraulic problem of significant importance to water engineers interested in determining the upstream and downstream influence of in-stream structures or works.

…”
mentioning
confidence: 99%
“…The paper by Zhang et al (2014) presents a three-dimensional numerical modelling study of the complex flow fields generated by multi-horizontal submerged jets discharging into a stilling basin. This has been proposed as a new type of energy dissipater for hydropower stations with high water heads and large unit discharges.…”
mentioning
confidence: 99%